Gender Disparities in Blood Pressure and the Role of Body Mass Index: A Birth Cohort Analysis in China - Jinjing Wu; Boshen Jiao; Jiaying Zhao (Springer, 2023)
Abstract Background The slow decline in cardiovascular disease (CVD) mortality and the stagnant or increasing hypertension prevalence in low- and middle-income countries necessitate investigation. Evolving gender disparities suggested that male cardiovascular health disadvantage may be preventable, offering potential for enhancing population cardiovascular health. Despite global body mass index (BMI) increases, its role in shaping the gender disparities remains underexplored. Objective This study investigated the birth cohort dynamics of gender disparities in systolic/diastolic blood pressure (SBP/DBP) in China, one of the world's largest low- and middle-income countries, and explored the potential role of BMI in explaining the changing gender disparities. Methods Data from the China Health and Nutrition Survey (1991-2015) were analyzed using multilevel growth-curve models to estimate gender- and cohort-specific SBP/DBP trajectories among individuals born between 1950 and 1975. Results Men had higher SBP and DBP than women at the sample's mean age of 41.7 years. The gender disparities in SBP and DBP increased with each successive one-year cohort from 1950 to 1975 by 0.14 mm Hg and 0.09 mm Hg, respectively. Adjusting for BMI reduced the increasing gender disparities in SBP and DBP by 31.9% and 34.4%, respectively. Conclusion Chinese men experienced a greater increase in SBP/DBP across successive cohorts compared to women. The increasing gender disparities in SBP/DBP were partially attributable to a greater BMI increase across cohorts among men. Given these findings, prioritizing interventions that aim to reduce BMI, particularly among men, could potentially alleviate the burden of CVD in China through lowering SBP/DBP.